Spatial clusters and temporal trends of cutaneous malignant melanoma mortality in Spain - Lucía Cayuela; José-Juan Pereyra-Rodriguez; Juan-Carlos Hernández-Rodríguez; Aurelio Cayuela (Journal of International Medical Research)
Objective To analyse time trends in mortality due to cutaneous malignant melanoma (CMM) in Spain between 1980 and 2020, and to identify possible spatial clusters of provinces with an excess risk of CMM mortality during the period 2011–2020. Methods Joinpoint regression models were used to assess temporal trends in data from the Spanish National Institute of Statistics. Crude rates, standardized mortality ratio (SMR), smoothed relative risk (RR), and posterior probabilities (PP) of RR >1 during the period 2011–2020 were calculated. The Global Moran I index was used to assess global spatial autocorrelation. Results Two time-periods were detected in women: a significant increase during 1980–1994 (annual percent change [APC], 6.5% per year) and rate stabilization during 1994–2020 (nonsignificant APC, −0.17%). A similar pattern was observed in men, with three periods comprising a significant increase during 1980–1985 (APC, 16.59%), a slowing of the increase during 1985–1998 (APC, 4.40%), and stabilization during 1998–2020 (nonsignificant APC, 0.37%). Spatial analysis showed greater spatial heterogeneity with an east-north pattern in men compared with the pattern in women, which tended to be concentrated in north-western areas. Conclusion Mortality rates associated with CMM in Spain have remained stable in recent years. There were provincial clusters that exhibited an excess risk of mortality from CMM, with different patterns according to sex.